Exploring thermally induced states in square artificial spin-ice arrays - J M Porro; A Bedoya-Pinto; A Berger; P Vavassori (New Journal of Physics, 2013)
We present a methodology to explore experimentally the formation of thermally induced long-range ground-state ordering in artificial spin-ice systems. Our novel approach is based on the thermalization from a square artificial spin-ice array of elongated ferromagnetic nanoislands made of a FeNi alloy characterized by a Curie temperature about 100 K lower than that of Permalloy (Ni _81 Fe _19 ), which is commonly used for this kind of investigation. The decrease in M ( T ) when the sample is heated close to its Curie temperature reduces the shape anisotropy barrier of each island and allows us to bring the artificial spin-ice pattern above the blocking temperature of the islands, thus ‘melting’ the spin-ice system, without damaging the sample. The magnetization configuration resulting from the thermal excitation of the islands and the frustrated dipolar interactions among them can be then imaged by magnetic force microscopy or any other kind of magnetic microscopy imaging after cooling down the sample back to room temperature. This thermally induced melting–freezing protocol can be repeated as many times as desired on the same sample and the heating and cooling parameters (max T , heating and cooling rates, number of cycles, application of external fields) varied at will. Thereby, the approach proposed here opens up a pathway to the systematic experimental study of thermally induced frozen states in artificial spin-ice systems, which have been the subject of many recent theoretical studies due to their interesting physical properties but, because of the difficulties in obtaining them in real samples and in a controlled manner, remain experimentally an almost completely unexplored terrain.